Structural properties of silica gels prepared from oxalic-acid-catalyzed tetraethoxysilane sonohydrolysis - Donatti, D. A.; Ibanez Ruiz, A.; Vicelli, M. R.; Vollet, D. R. (Wiley-Blackwell, 2007)
About similar to 2.1 x 10(-3) Mol SiO2 cm(-3) and similar to 88%-volume liquid-phase silica wet gels were prepared from oxalic-acid-catalyzed tetraethoxysilane (TEOS) sonohydrolysis. Aerogels were obtained by supercritical CO2 extraction. The samples were analyzed by thermogravimetry, small-angle X-ray scattering and nitrogen adsorption. Wet gels can be described as mass fractal structures with fractal dimension D similar to 1.94 and structural characteristic length zeta changing between similar to 3.3 to similar to 3.0 nm in the studied range of the catalyst concentration. A fraction of the porosity is apparently eliminated in the supercritical process. The values of the BET specific surface S-BET, the total pore volume V-p and the mean pore size l(p) of the aerogels were found to change almost randomly around the mean values S-BET = 874 m(2) g(-1), V-p = 0.961 cm(3) g(-1) and l(p) = 4.4 nm with catalyst concentration variation. These values were not substantially different from those from an equivalent HCl-catalyzed aerogel. (c) 2007 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.